2004
DOI: 10.1021/ja031558k
|View full text |Cite
|
Sign up to set email alerts
|

ansa-Zirconocene Ester Enolates:  Synthesis, Structure, Reaction with Organo-Lewis Acids, and Application to Polymerization of Methacrylates

Abstract: The synthesis, structural characterization, and abstraction chemistry of ansa-zirconocene ester enolate complexes relevant to the isospecific polymerization of methacrylates are reported. Reactions of rac-(EBI)ZrMe(OTf) and rac-(EBI)Zr(OTf)(2) [EBI = C(2)H(4)(Ind)(2)] with 1 and 2 equiv of lithium isopropylisobutyrate in toluene produce the first examples of ansa-zirconocene mono- and diester enolate complexes: rac-(EBI)ZrMe[OC(O(i)Pr)=CMe(2)] (1) and rac-(EBI)Zr[OC(O(i)Pr)=CMe(2)](2) (2) in 89% and 50% isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
114
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 50 publications
10
114
0
1
Order By: Relevance
“…For instance, the polymerization of allyl methacrylate (AMA) by half-metallocene yttrium catalysts was shown to be both living and chemoselective. 11 Furthermore, a chiral C 2 -ligated ansa-zirconocenium ester enolate complex, [rac-C 2 H 4 (η 5 -indenyl) 2 3 ] − (1), 12 which is known to mediate stereospecific and living polymerization of simple alkyl methacrylates such as methyl methacrylate (MMA) 12,13 and acrylamides, 14 is not only completely chemoselective and living, but also highly isospecific, in the polymerization of polar divinyl monomers at ambient temperature. 15 The origin of the perfect chemoselectivity and high isoselectivity arises from the catalyst site-controlled coordinationaddition mechanism that dictates exclusive conjugate additions across the methacrylic double bond that is activated via coordination of the conjugated carbonyl to the cationic, chiral Zr center, thus leaving the pendant C=C bond intact.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the polymerization of allyl methacrylate (AMA) by half-metallocene yttrium catalysts was shown to be both living and chemoselective. 11 Furthermore, a chiral C 2 -ligated ansa-zirconocenium ester enolate complex, [rac-C 2 H 4 (η 5 -indenyl) 2 3 ] − (1), 12 which is known to mediate stereospecific and living polymerization of simple alkyl methacrylates such as methyl methacrylate (MMA) 12,13 and acrylamides, 14 is not only completely chemoselective and living, but also highly isospecific, in the polymerization of polar divinyl monomers at ambient temperature. 15 The origin of the perfect chemoselectivity and high isoselectivity arises from the catalyst site-controlled coordinationaddition mechanism that dictates exclusive conjugate additions across the methacrylic double bond that is activated via coordination of the conjugated carbonyl to the cationic, chiral Zr center, thus leaving the pendant C=C bond intact.…”
Section: Introductionmentioning
confidence: 99%
“…[4,8,31] We have investigated the reactivity of complexes 2a-b and 3a-b with the Lewis acids E(C 6 F 5 ) 3 (E = B, Al) with the aim of abstracting the alkyl ligand to generate a cationic enolate compound, considering that early transition-metal derivatives of this type have been used as precursors for the catalytic polymerization of acrylates. [12][13][14][15][16] Although the nucleophilicity of the oxygen atom bonded to the niobium atom could compete with that of the carbon atom, we have previously observed that alkoxido complexes of the type [Cp*TaMe 3 (OR)] reacted with these Lewis acids E(C 6 F 5 ) 3 at the Ta-C bond. [32] Furthermore, Mashima and co-workers also reported that reaction of the MMA complex [TaCp*(DAD)(MMA)] [DAD = N(R) CH=CHN(R)] with AlMe 3 produced the activation of the Ta-C bond of the coordinated MMA ligand.…”
Section: (E = B Al)mentioning
confidence: 99%
“…The study of enolate derivatives has attracted attention because they have been proposed as the active species for polymerization of polar monomers. [11][12][13][14][15][16] Another feature of these compounds is that coordination of the asymmetric α,β-unsaturated carbonyl ligands will create two new reactive points in the molecule at the M-C and M-O bonds.…”
Section: Introductionmentioning
confidence: 99%
“…All purified monomers were stored in brown bottles and stored inside a glovebox freezer at À30 C. The B(C 6 F 5 ) 3 Á THF adduct was prepared by addition of THF to a toluene solution of the borane followed by removal of the volatiles and drying in vacuo. Literature procedures were employed for the preparation of the following neutral pre-catalysts and the corresponding cationic catalysts: [Ph 2 C(Cp)(2,7- [9] {rac…”
Section: Introductionmentioning
confidence: 99%
“…[9] General Polymerization Procedures MMA Polymerizations were performed either in 25-mL flame-dried Schlenk flasks interfaced to the dual-manifold Schlenk line for runs using external temperature bath, or in 30-mL glass reactors inside the glovebox for ambient temperature (ca. 25 C) runs.…”
Section: Introductionmentioning
confidence: 99%